Alpha-MoO3 crystal growth fluxing agent and crystal growth method

By using the flux method of ZnO-TeO2 composite flux system in a high-temperature molten salt furnace to grow α-MoO3 crystals, the problems of complex equipment, high cost and poor crystal quality in the prior art are solved, and high-quality α-MoO3 single crystals are prepared at low cost and high efficiency.

CN119877080APending Publication Date: 2025-04-25TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510074844.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In the prior art, methods for growing α-MoO3 crystals such as PVD methods have problems such as complex equipment, harsh preparation conditions, high cost, polluted environment, irregular crystal shape, small size, thin thickness and poor quality, and cannot meet the actual application needs.

Method used

The flux method is adopted, and the ZnO-TeO2 composite flux system is used to grow α-MoO3 crystals in a high-temperature molten salt furnace through spontaneous crystallization or top crystallization method, reducing growth temperature and energy consumption, and improving the quality and yield of the crystal.

Benefits of technology

It realizes the batch preparation of centimeter-level, high-quality α-MoO3 single crystals in low-cost, fast, safe and environmentally friendly manner, reduces the crystal growth temperature and energy consumption, and improves the quality and yield of the crystals. It is suitable for photocatalysis, electrode materials and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877080A_ABST
    Figure CN119877080A_ABST
Patent Text Reader

Abstract

The invention provides an alpha-MoO3 crystal growth fluxing agent and a crystal growth method, alpha-MoO3 is used as a raw material, a ZnO-TeO2 system is used as the fluxing agent, and crystal growth is carried out by adopting a fluxing agent method. The growth temperature of the crystal is 550-600 DEG C, the volatility of a growth system is relatively small, no mixed crystal appears in the growth process of the crystal, and the stability of the system is relatively high; meanwhile, the high-temperature solution is clear and transparent during growth, the crystal growth condition can be observed in real time, and growth parameters are convenient to adjust. The method is simple in equipment and process, good in repeatability, low in cost and stable and reliable in operation. The alpha-MoO3 crystal prepared by the method has the advantages of regular morphology, large size, high yield, high crystal quality and the like, and meanwhile, the alpha-MoO3 crystal prepared by the method has wide application in the fields of photocatalysis, electrode materials, photoelectric detectors, gas sensors, field effect transistors and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of oxide crystal growth, and in particular relates to an alpha-MoO3 crystal growth flux and a crystal growth method. Background Art

[0002] Molybdenum trioxide (MoO3) is an important class of transition metal oxide semiconductors. MoO3 has three common crystal phase structures, including thermodynamically stable orthorhombic α-MoO3, thermodynamically metastable monoclinic β-MoO3 and hexagonal h-MoO3. Among them, α-MoO3 is a layered wide bandgap semiconductor material (E g= 3.05eV), the layers are connected by weak van der Waals forces and can be thinned by peeling, while the structure is bonded by strong covalent and ionic bonds. The unit cell of a single layer of α-MoO3 is composed of a double layer of edge-sharing [MoO6] octahedrons with a thickness of about 0.7nm. MoO6 has three different O atoms, including terminal oxygen O t , double coordinated asymmetric bridging oxygen O a , three-coordinate symmetric bridging oxygen O s The distance between Mo atoms in the layers is 1.4 nm, which is the thickness of a single layer of α-MoO3. The edge-sharing MoO6 regular octahedrons in the planar double layer are arranged in a zigzag pattern along the

[001] direction, while the oxygen atoms are center-shared along the

[100] direction.

[0003] α-MoO3 has the characteristics of high specific surface area and porosity, photochromism, electrochromism, photocatalytic degradation, gas sensitivity and excellent optical properties, electrochemical properties, etc. Therefore, α-MoO3 has been widely used in photochromic devices, electrochromic devices, gas sensors, photodetectors, field effect transistors, electrode materials, catalysts and other fields.

[0004] At present, the preparation methods of α-MoO3 crystals mainly include hydrothermal method, electron beam evaporation, pulsed laser deposition, chemical vapor deposition, physical vapor deposition, etc.

[0005] The crystals synthesized by the hydrothermal method are small in size and low in yield, and the impurities and defects introduced during the synthesis process are not suitable for applications such as optoelectronic devices. The α-MoO3 film obtained by the electron beam evaporation method is a polycrystalline film with shortcomings such as poor electrical properties and many defects. The deposition equipment required for the pulsed laser deposition method is expensive, the vacuum degree is high, the preparation process is harsh, the energy consumption is high, and the yield is low. The α-MoO3 crystals synthesized by the chemical vapor deposition method are small in size, low in yield, and the crystal quality is poor.

[0006] Physical vapor deposition (PVD) is currently the most important growth method for α-MoO3 crystals. In 2018, Zheng et al. used the PVD method to grow α-MoO3 single crystals. The specific steps are: a 3 cm long quartz tube filled with α-MoO3 powder is placed in the heating zone of the tube furnace, and a 12 cm long quartz boat is placed in the cold zone of the tube furnace. The distance between the quartz tube and the quartz boat is 15 cm, and the growth is carried out in an oxygen atmosphere. The heating zone is heated to 850-1050°C at a heating rate of 25°C / min and maintained for 30 minutes. The α-MoO3 powder evaporates at high temperature and then recrystallizes and is deposited in the quartz boat. Then the heating is stopped and the furnace is immediately opened to cool down. The maximum size of the obtained α-MoO3 crystal is about 10×3mm 2 (Binjie Zheng, Zegao Wang, Yuanfu Chen, et al. Centimeters-sized 2D α-MoO3 single crystal: growth, raman anisotropy, and optoelectronic properties, 2D Materials, 5 (2018) 045011.) In 2019, Sun et al. used PVD to grow α-MoO3 single crystals in an argon atmosphere and placed a Φ2×20 cm 3 The quartz tube is placed in the heating zone with a size of Φ8×20cm 3 In a tube furnace, the flow rate of carrier gas argon is 60sccm. The heating zone is first heated to 710℃ at a heating rate of 20℃ / min, and then heated to 750℃ at a rate of 2℃ / min. After the growth is completed, it is cooled to room temperature. α-MoO3 crystals with sizes ranging from microns to millimeters are obtained at one end of the quartz tube. The maximum size of the crystal is 8×9×0.1mm 3 (Haoliang Sun, Huan Zhang, Xinxin Jing, et al. One-step synthesis of centimeter-size alpha-MoO3 with single crystallinity, Applied Surface Science, 476 (2019) 789-795.). In 2022, Li et al. used PVD method to grow α-MoO3 single crystal in a double temperature zone tube furnace. The carrier gas was air with a flow rate of 120 sccm. The α-MoO3 powder was placed in a high temperature zone of 750°C. After the α-MoO3 powder was heated and vaporized, it was recrystallized and deposited in a low temperature zone of 550°C. The maximum size of the obtained α-MoO3 crystal was 20×5 mm 2, the crystal thickness is too thin to be self-supporting (Wei Li, Qingdong Ou, Xiaodong Wang, et al. Large-sized α-MoO3layered single crystals for superior NO2gas sensing, Applied Surface Science, 586 (2022) 152793.).

[0007] However, the tubular furnace used in the PVD method includes heating, gas path, exhaust and control system, etc., with complex structure, high difficulty in operation and harsh preparation conditions. The tubular furnace used in the PVD method has no observation window, which is a "blind burning" method. It is impossible to observe the crystal growth status in real time, adjust the growth parameters in time, and guarantee the quality of the crystal. The PVD method requires the α-MoO3 raw material to be heated to above 750°C for gasification, which consumes a lot of energy and has high cost. In order to ensure the normal growth of the crystal, it is necessary to introduce inert gas and other carrier gases. The price of carrier gas is high, and waste gas will be discharged during the crystal growth process, polluting the environment. Moreover, the flowing carrier gas will take away the ungasified α-MoO3 powder particles and deposit them in the low temperature zone, resulting in the introduction of amorphous substances in the growing α-MoO3 crystals, making the grown crystals low in crystallinity, many defects and poor in quality. In addition, the crystallization rate of the PVD method is too fast, the grown α-MoO3 crystals are irregular in shape, small in crystal size, thin in thickness, and low in utilization rate, which cannot meet the requirements of device manufacturing.

[0008] In summary, the PVD method is currently the mainstream method for growing α-MoO3 crystals, but this method has complex equipment, harsh preparation conditions, high cost, and environmental pollution. The grown crystals are irregular in shape, small in size, thin in thickness, and of poor quality, which cannot meet the needs of actual applications.

[0009] The flux method, also known as the high-temperature solution method, is an important crystal growth method. It refers to a method of growing crystals from a molten solution at high temperature. This method can make the crystal grow at a temperature below its melting point. The flux method includes the spontaneous crystallization method and the top seed method. At present, there is no report on the growth of α-MoO3 crystals using the flux method at home and abroad. Summary of the invention

[0010] In view of the deficiencies in the prior art methods, the purpose of the present invention is to provide a low-cost, rapid, safe and environmentally friendly method for batch preparation of centimeter-level, high-quality α-MoO3 single crystals.

[0011] The invention provides an alpha-MoO3 crystal growth flux and a crystal growth method, and adopts a flux method for the first time to grow alpha-MoO3 crystals to obtain high-quality single crystals.

[0012] The present invention adopts a composite flux to grow alpha-MoO3 crystals, and the flux system is ZnO-TeO2.

[0013] Preferably, the molar ratio of α-MoO3:ZnO:TeO2 is 1:(0.1-2.0):(0.5-6).

[0014] Preferably, the compound ZnO can be ZnF2, ZnCO3, ZnCl2, ZnSO3, ZnSO4, ZnSO4·7H2O, Zn3(PO4)2, Zn(NO3 )2·6H2O, Zn(C2H3O2)2.H2O, Zn(OH)2, Zn(NO3)2, Zn(NO2)2, Zn(ClO)2, Zn(ClO2)2, Zn(BrO2)2, Zn(IO2)2, Zn(C2H3O2)2, Zn(HCO3)2, Zn(ClO3)2, Zn(BrO3)2, Zn(IO3) 2. Replacement of Zn(ClO4)2, Zn(BrO4)2, Zn(IO4)2, Zn3(PO3)2, Zn(H2PO4)2, ZnC2O4 or ZnCr2O7.

[0015] Preferably, the compound TeO2 can be replaced by TeCl4, (NH4)2TeO4 or TeF4.

[0016] The present invention also provides a method for growing α-MoO3 crystals, which, if a spontaneous crystallization method is adopted, comprises the following steps:

[0017] (a) preparing and uniformly mixing the ingredients according to the molar ratio of α-MoO3:ZnO:TeO2 of 1:(0.1-2.0):(0.5-6), placing the ingredients in a high-temperature molten salt furnace and heating them to 650-700°C at a rate of 10-50°C / h to melt the ingredients, thereby obtaining a crystal growth raw material;

[0018] (b) Stirring at a constant temperature for 24 to 48 hours, removing the stirrer, and cooling to 550 to 600° C. at a rate of 1 to 10° C. / h. Crystals precipitate from the surface of the high-temperature solution, and the crystallization temperature is determined to be 550 to 600° C.;

[0019] (c) Using the crystallization temperature of the high temperature solution as the starting temperature for cooling, slowly cooling at a rate of 0.5 to 5°C / day to allow the crystals to grow;

[0020] (d) After the crystal grows to the desired size, use a platinum scoop to scoop the crystal out of the liquid surface and cool it to room temperature at a rate of 5 to 20°C / h to obtain α-MoO3 crystals; or slowly pour out the high-temperature solution in the crucible to obtain α-MoO3 crystals.

[0021] Preferably, in step (a), a platinum crucible is used to hold the uniformly mixed raw materials.

[0022] Preferably, the agitator in step (b) is a platinum stirring paddle.

[0023] The present invention also provides a method for growing α-MoO3 crystals, which, if a top seeding method is adopted, comprises the following steps:

[0024] (a) preparing and uniformly mixing the o-MoO3:ZnO:TeO2 in a molar ratio of 1:(0.1-2.0):(0.5-6), placing the mixture in a high-temperature molten salt furnace and heating the mixture to 650-700°C at a rate of 10-50°C / h to obtain a raw material for crystal growth;

[0025] (b) Stirring at a constant temperature for 24 to 48 hours, removing the stirrer, cooling to 550 to 600° C., selecting a transparent α-MoO3 single crystal as a seed crystal, fixing the seed crystal on a seed crystal rod with a platinum wire, and determining the saturation point temperature by a trial seed crystal method;

[0026] (c) introducing the seed crystal fixed on the seed crystal rod into the liquid surface at a temperature 1 to 3°C above the saturation point temperature, maintaining the temperature at a constant temperature for 30 to 60 minutes, and then cooling the temperature to the saturation point temperature;

[0027] (d) using the saturation point temperature as the starting temperature for cooling, slowly cooling at a rate of 0.2 to 1°C / day, while rotating the crystal at a rate of 5 to 30 rpm to allow the crystal to grow;

[0028] (e) After the crystal grows to the desired size, the seed crystal rod is lifted to separate the crystal from the liquid surface, and the temperature is cooled to room temperature at a rate of 5 to 10°C / h to obtain α-MoO3 crystal.

[0029] Preferably, in step (a), a platinum crucible is used to hold the uniformly mixed raw materials.

[0030] Preferably, the agitator in step (b) is a platinum stirring paddle.

[0031] Preferably, in step (c), the direction of the seed crystal is

[010] ,

[100] or

[001] .

[0032] Preferably, in step (d), the crystal rotation direction is unidirectional rotation or bidirectional rotation.

[0033] Preferably, in the step (d), if the crystal is rotated in a bidirectional direction, the rotation mode is alternating clockwise and counterclockwise, and the rotation is performed according to the following cycle: accelerating rotation, rotating at a constant speed, decelerating rotation and stopping rotation in a first direction, and then accelerating rotation, rotating at a constant speed, decelerating rotation and stopping rotation in a second direction opposite to the first direction. In the bidirectional rotation, the rotation time in each direction is 1 to 3 minutes, and the interval time of the bidirectional rotation is 0.1 to 0.5 minutes.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention adopts the flux method for crystal growth for the first time. The crystal growth equipment is a high-temperature molten salt furnace with a simple structure, safety and reliability, convenient operation, and easy maintenance. Crystal growth can be carried out in an air atmosphere, and the requirements for the growth environment are low. The furnace cover is equipped with an observation window, which can observe the crystal growth status and adjust the growth parameters in time. Oxides are commonly used fluxes in crystal growth. In the present invention, ZnO and TeO2 composite fluxes are introduced, and the coupling synergistic effect of multiple raw materials is utilized to effectively reduce the crystal growth temperature, reduce the viscosity and volatility of the growth system, and improve the stability of the growth system:

[0036] (1) Compared with the PVD method, the flux method can effectively lower the crystal growth temperature to between 550 and 600 °C, thereby reducing energy consumption and the difficulty of crystal growth.

[0037] (2) The crystal growth temperature is low, and the high-temperature solution is clear and transparent. The crystal morphology and quality can be visually understood in real time, and growth parameters such as cooling rate and rotation speed can be optimized in time to obtain high-quality single crystals.

[0038] (3) The crystal growth temperature is low, the volatility of the system is low, and there are fewer volatiles, which can prevent the volatiles from falling into the liquid surface to form stray crystals, thereby improving the stability of the growth system and thus increasing the success rate of crystal growth.

[0039] (4) In the flux method, under the dual effects of high temperature and flux, the solution viscosity can be significantly reduced, which is beneficial to the transfer of melt and heat, increases the crystal growth rate, and reduces the generation of crystal defects such as inclusions and dislocations.

[0040] (5) In the flux method, when the spontaneous crystallization method is adopted, there are multiple nucleation points on the liquid surface, and multiple block-shaped transparent crystals will precipitate. These crystals gradually grow and can be self-supporting, thereby improving the yield.

[0041] (6) In the flux method, the crystallization area and cooling range of the crystal are larger, and a series of regular-shaped, centimeter-level, thick, high-quality α-MoO3 crystals can be repeatedly and stably grown, which significantly improves the preparation efficiency.

[0042] (7) The large-sized, high-quality α-MoO3 crystals prepared by the present invention have broad application prospects in the fields of photocatalysis, electrode materials, photodetectors, gas sensors, field effect transistors, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a photograph of the large-sized α-MoO3 crystals prepared in Example 1.

[0044] Figure 2 This is a photograph of the large-sized α-MoO3 crystal prepared in Example 2 after cutting and processing.

[0045] Figure 3 This is the powder X-ray diffraction test spectrum of the α-MoO3 crystal prepared in Example 2.

[0046] Figure 4 This is the single crystal X-ray diffraction test spectrum of the α-MoO3 crystal prepared in Example 2.

[0047] Figure 5 This is the transmission spectrum of the α-MoO3 crystal prepared in Example 2.

[0048] Figure 6 This is the single crystal rocking curve test spectrum of the α-MoO3 crystal prepared in Example 2. DETAILED DESCRIPTION

[0049] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0050] Example 1

[0051] α-MoO3 crystals were grown by spontaneous crystallization method: 143.96 g α-MoO3, 24.41 g ZnO, and 207.48 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ60×60mm 3 Place the platinum crucible in a single-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Heat up to 650°C at a heating rate of 40°C / h to completely melt the raw materials, stir at a constant temperature for 36 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down at a cooling rate of 6°C / h until crystals precipitate on the liquid surface, and determine that the crystallization temperature is 563°C. Take the crystallization temperature of the high-temperature solution as the starting temperature for cooling, and slowly cool down at a cooling rate of 0.5-5°C / day to allow the crystals to grow. After 36 days of crystal growth, the crucible is directly taken out, and the high-temperature solution is slowly poured out. A large number of α-MoO3 crystals remain in the crucible, with the maximum size reaching Φ30×12×0.8mm 3 . The crystal has a regular shape and is transparent inside.

[0052] Example 2

[0053] α-MoO3 crystals were grown by top crystallization method: 143.96 g α-MoO3, 24.41 g ZnO, and 207.48 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ80×80mm 3Place the platinum crucible in a three-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Heat up to 680°C at a heating rate of 25°C / h to completely melt the raw materials, stir at a constant temperature for 24 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down to 550-600°C, fix the seed crystal on the seed crystal rod with a platinum wire, and use the trial seed crystal method to determine the saturation point temperature, which is 565°C. Heat up to 1°C above the saturation point temperature, select the

[010] transparent α-MoO3 single crystal as the seed crystal, introduce the seed crystal fixed on the seed crystal rod into the liquid surface, keep the temperature constant for 30 minutes, and then cool down to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2-1°C / day, while the crystal was rotated at a rate of 5-30rpm to grow. After 30 days of crystal growth, the seed crystal rod was lifted to separate the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 5°C / h to obtain a crystal with a size of Φ43×12×0.6mm 3 α-MoO3 single crystal. The crystal has a regular shape and is transparent inside.

[0054] Example 3

[0055] α-MoO3 crystals were grown by spontaneous crystallization method: 143.96 g α-MoO3, 40.69 g ZnO, and 239.40 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ60×60mm 3 Place it in a platinum crucible and put it into a single-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Raise the temperature to 700°C at a heating rate of 35°C / h to completely melt the raw materials, stir at a constant temperature for 48 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down at a cooling rate of 5°C / h until crystals precipitate on the liquid surface, and determine that the crystallization temperature is 556°C. Take the crystallization temperature of the high-temperature solution as the starting temperature for cooling, and slowly cool at a cooling rate of 0.5-5°C / day to allow the crystals to grow. After 12 days of crystal growth, the crystals are removed from the liquid surface with a platinum scoop net and cooled to room temperature at a rate of 5°C / h to obtain a maximum size of Φ8×5×0.3mm 3 α-MoO3 single crystal. The crystal has a regular shape and is transparent inside.

[0056] Example 4

[0057] α-MoO3 crystals were grown by spontaneous crystallization method: 143.96 g α-MoO3, 81.38 g ZnO, and 478.79 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ100×100mm 3Place the platinum crucible in a single-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Heat up to 680°C at a heating rate of 40°C / h to completely melt the raw materials, stir at a constant temperature for 48 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down at a cooling rate of 5°C / h until crystals precipitate on the liquid surface, and determine that the crystallization temperature is 550°C. Take the crystallization temperature of the high-temperature solution as the starting temperature for cooling, and slowly cool down at a cooling rate of 0.5 to 5°C / day to allow the crystals to grow. After 18 days of crystal growth, the crucible is directly taken out, and the high-temperature solution is slowly poured out. A large number of α-MoO3 crystals remain in the crucible, with the maximum size reaching Φ20×6×0.4mm 3 . The crystal has a regular shape and is transparent inside.

[0058] Example 5

[0059] α-MoO3 crystals were grown by spontaneous crystallization method: 143.96 g α-MoO3, 122.07 g ZnO, and 638.39 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ100×100mm 3 Place it in a platinum crucible and put it into a single-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Raise the temperature to 665°C at a heating rate of 25°C / h to completely melt the raw materials, stir at a constant temperature for 36 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down at a cooling rate of 5°C / h until crystals precipitate on the liquid surface, and determine that the crystallization temperature is 552°C. Take the crystallization temperature of the high-temperature solution as the starting temperature for cooling, and slowly cool at a cooling rate of 0.5-5°C / day to allow the crystals to grow. After 33 days of crystal growth, the crystals are removed from the liquid surface with a platinum scoop net and cooled to room temperature at a rate of 10°C / h to obtain a maximum size of Φ35×12×0.4mm 3 α-MoO3 single crystal. The crystal has a regular shape and is transparent inside.

[0060] Example 6

[0061] α-MoO3 crystals were grown by top crystallization method: 143.96 g α-MoO3, 162.76 g ZnO, and 957.59 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ100×100mm 3Place the platinum crucible in a three-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Heat up to 670°C at a heating rate of 30°C / h to completely melt the raw materials, stir at a constant temperature for 48 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down to 550-600°C, fix the seed crystal on the seed crystal rod with a platinum wire, and use the trial seed crystal method to determine the saturation point temperature, which is 551°C. Heat up to 2°C above the saturation point temperature, select the

[010] transparent α-MoO3 single crystal as the seed crystal, introduce the seed crystal fixed on the seed crystal rod into the liquid surface, keep the temperature constant for 40 minutes, and then cool down to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2-1°C / day, while the crystal was rotated at a rate of 5-30rpm to grow. After 23 days of crystal growth, the seed crystal rod was lifted to separate the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 10°C / h to obtain a crystal with a size of Φ28×8×0.4mm 3 α-MoO3 single crystal. The crystal has a regular shape and is transparent inside.

[0062] Example 7

[0063] α-MoO3 crystals were grown by top crystallization method: 143.96 g α-MoO3, 8.14 g ZnO, and 79.80 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ60×60mm 3 Place the platinum crucible in a single-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Heat up to 670°C at a heating rate of 20°C / h to completely melt the raw materials, stir at a constant temperature for 48 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down to 550-600°C, fix the seed crystal on the seed crystal rod with a platinum wire, and use the trial seed crystal method to determine the saturation point temperature, which is 596°C. Heat up to 1°C above the saturation point temperature, select the

[001] transparent α-MoO3 single crystal as the seed crystal, introduce the seed crystal fixed on the seed crystal rod into the liquid surface, keep the temperature constant for 30 minutes, and then cool down to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2-1°C / day, while the crystal was rotated at a rate of 5-30rpm to grow. After 11 days of crystal growth, the seed crystal rod was lifted to separate the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 5°C / h to obtain a crystal with a size of Φ16×7×0.3mm 3 α-MoO3 single crystal. The crystal has a regular shape and is transparent inside.

[0064] Example 8

[0065] α-MoO3 crystals were grown by top crystallization method: 143.96 g α-MoO3, 16.28 g ZnO, and 159.60 g TeO2 were ground in an agate mortar and mixed evenly, and then loaded into a Φ80×80mm 3 Place the platinum crucible in a three-stage high-temperature molten salt furnace heated by a resistance wire. Center the platinum crucible to ensure that the center of the crucible coincides with the center of the crystal furnace, install a platinum stirring paddle, cover the furnace cover, and cover the observation hole on the furnace cover with quartz glass. Heat to 690°C at a heating rate of 30°C / h to completely melt the raw materials, stir at a constant temperature for 48 hours, and remove the stirring paddle after the high-temperature solution is fully uniform. Cool down to 550-600°C, fix the seed crystal on the seed crystal rod with a platinum wire, and use the trial seed crystal method to determine the saturation point temperature, which is 580°C. Heat to 2°C above the saturation point temperature, select the

[010] transparent α-MoO3 single crystal as the seed crystal, introduce the seed crystal fixed on the seed crystal rod into the liquid surface, keep the temperature constant for 30 minutes, and then cool to the saturation point temperature. The saturation point temperature was used as the starting temperature for cooling, and the temperature was lowered at a rate of 0.2-1°C / day, while the crystal was rotated at a rate of 5-30rpm to grow. After 34 days of crystal growth, the seed crystal rod was lifted to separate the crystal from the liquid surface, and the temperature was lowered to room temperature at a rate of 5°C / h to obtain a crystal with a size of Φ39×15×0.5mm 3 α-MoO3 single crystal. The crystal has a regular shape and is transparent inside.

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the technical principles of the present invention. These improvements and substitutions should also be regarded as the scope of protection of the present invention.

Claims

1. A large-size α-MoO3 crystal growth flux, characterized in that: α-MoO3 powder is used as raw material and ZnO-TeO2 system is used as flux; The molar ratio of α-MoO3:ZnO:TeO2 is 1:(0.1~2.0):(0.5~6).

2. The flux system according to claim 1, characterized in that Compound ZnO can be used as ZnF2, ZnCO3, ZnCl2, ZnSO3, ZnSO4, ZnSO4·7H2O, Zn3(PO4)2, Zn(NO3)2· 6H2O, Zn(C2H3O2)2.H2O, Zn(OH)2, Zn(NO3)2, Zn(NO2)2, Zn(ClO)2, Zn(ClO2)2, Zn (BrO2)2, Zn(IO2)2, Zn(C2H3O2)2, Zn(HCO3)2, Zn(ClO3)2, Zn(BrO3)2, Zn(IO3)2 , Zn(ClO4)2, Zn(BrO4)2, Zn(IO4)2, Zn3(PO3)2, Zn(H2PO4)2, ZnC2O4 or ZnCr2O7 instead.

3. The flux system according to claim 1, characterized in that The compound TeO2 can be replaced by TeCl4, (NH4)2TeO4 or TeF4.

4. A flux growth method for α-MoO3 crystals according to claim 1, characterized in that: If the spontaneous crystallization method is used to obtain α-MoO3 crystals, the following steps are included: (a) preparing and uniformly mixing the ingredients according to the molar ratio of α-MoO3:ZnO:TeO2 of 1:(0.1-2.0):(0.5-6), placing the ingredients in a high-temperature molten salt furnace and heating them to 650-700°C at a rate of 10-50°C / h to melt the ingredients, thereby obtaining a crystal growth raw material; (b) Stirring at a constant temperature for 24 to 48 hours, removing the stirrer, and cooling to 550 to 600° C. at a rate of 1 to 10° C. / h. Crystals precipitate from the surface of the high-temperature solution, and the crystallization temperature is determined to be 550 to 600° C.; (c) Using the crystallization temperature of the high temperature solution as the starting temperature for cooling, slowly cooling at a rate of 0.5 to 5°C / day to allow the crystals to grow; (d) After the crystal grows to the desired size, use a platinum scoop to scoop the crystal out of the liquid surface and cool it to room temperature at a rate of 5 to 20°C / h to obtain α-MoO3 crystals; or slowly pour out the high-temperature solution in the crucible to obtain α-MoO3 crystals.

5. A flux growth method for α-MoO3 crystals according to claim 1, characterized in that: If the top seed method is used to obtain α-MoO3 crystals, the following steps are included: (a) preparing and uniformly mixing the ingredients according to the molar ratio of α-MoO3:ZnO:TeO2 of 1:(0.1-2.0):(0.5-6), placing the ingredients in a high-temperature molten salt furnace and heating them to 650-700°C at a rate of 10-50°C / h to melt the ingredients, thereby obtaining a crystal growth raw material; (b) Stirring at a constant temperature for 24 to 48 hours, removing the stirrer, cooling to 550 to 600° C., selecting a transparent α-MoO3 single crystal as a seed crystal, fixing the seed crystal on a seed crystal rod with a platinum wire, and determining the saturation point temperature by a trial seed crystal method; (c) introducing the seed crystal fixed on the seed crystal rod into the liquid surface at a temperature 1 to 3°C above the saturation point temperature, maintaining the temperature at a constant temperature for 30 to 60 minutes, and then cooling the temperature to the saturation point temperature; (d) using the saturation point temperature as the starting temperature for cooling, slowly cooling at a rate of 0.2 to 1°C / day, while rotating the crystal at a rate of 5 to 30 rpm to allow the crystal to grow; (e) After the crystal grows to the desired size, the seed crystal rod is lifted to separate the crystal from the liquid surface, and the temperature is cooled to room temperature at a rate of 5 to 10°C / h to obtain α-MoO3 crystal.

6. The growth method according to claim 4 or 5, characterized in that: In the step (a), a platinum crucible is used to hold the uniformly mixed raw materials.

7. The growth method according to claim 4 or 5, characterized in that: The agitator in step (b) is a platinum stirring paddle.

8. The growth method according to claim 5, characterized in that: In the step (c), the direction of the seed crystal is [010], [100] or [001].

9. The growth method according to claim 5, characterized in that: In the step (d), the crystal rotation direction is unidirectional rotation or bidirectional rotation.

10. The growth method according to claim 5, characterized in that: If the crystal is rotated in a bidirectional direction in step (d), the rotation mode is alternating clockwise and counterclockwise, and the rotation is performed according to the following cycle: accelerating rotation, rotating at a constant speed, decelerating rotation and stopping rotation in a first direction, and then accelerating rotation, rotating at a constant speed, decelerating rotation and stopping rotation in a second direction opposite to the first direction. In the bidirectional rotation, the rotation time in each direction is 1 to 3 minutes, and the interval time of the bidirectional rotation is 0.1 to 0.5 minutes.

Citation Information

Patent Citations

  • Tellurium-caesium molybdate crystal, growth of tellurium-caesium molybdate crystal by flux method and application

    CN102011189A

  • Nonlinear optical material ZnTeMoO6, and growth method for ZnTeMoO6 crystal

    CN102534793A

  • Compound tellurium-zinc-lead arsenate and tellurium-zinc-lead arsenate nonlinear optical crystal as well as preparation method and application thereof

    CN110528080A

  • Method of growing single crystals

    CN1165543A

  • Beta-BaB2O4 crystal growth fluxing agent and crystal growth method

    CN116623273A